The Effectiveness of Honey-Based Ferric Perchloride Paste on Post-conization in the Cicatricial and Infectious Context: A Randomized Clinical Trial - Maestri, Carlos Afonso; Antoniazzi, Rodolfo Belz; Maestri, Isabela Ceschin; Fernandes, Rafaela Ceschin; Fonseca, Fernanda Villar (Clinical Journal of Obstetrics and Gynecology, 2023)
Introduction: The skills, the techniques utilized in the conization and the hemostasis directly affect the healing process of the cervix tissue. Excessively large excisions and unnecessary use of electrocautery or hemostatic sutures are examples of procedures that may negatively affect the scar cascade and wound healing. Objective: The purpose of this study was to examine the effectiveness of honey-based ferric perchloride paste (HBFPP) in reducing bleeding and infection post-conization procedure. Methods: Prospective randomized clinical trial with a sample of 142 patients randomized in two groups: 78 patients who used the HBFPP (intervention) and 64 patients who did not use the HBFPP (control). Statistical analysis was performed utilizing a significance level of 95%. The Chi-Square test and Fisher’s exact test were applied. Results: Results showed that the mean score of the amount of blood lost was lower in the intervention group compared to the control group. The main complaints reported by the two groups in the postoperative period were discomfort in the genitourinary system, heavy bleeding after surgery, and post-operative infection, but not significantly different among both groups. The control group needed further intervention due to excessive bleeding in comparison with the intervention group. Conclusion: The use of HBFPP reduced the amount of blood lost in the postoperative period of conization surgery.